2013
DOI: 10.1111/echo.12136
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Wall Thickness of the Left Anterior Descending Artery Using High Resolution Transthoracic Echocardiography – Normal Range of Values

Abstract: Recently it has been demonstrated that high resolution transthoracic echocardiography (HRTTE) is able to detect differences in the wall thickness of the left anterior descending coronary artery (LAD) between patients with coronary artery disease (CAD) and normal volunteers. We sought to validate this technique, develop a normal range of values and demonstrate the test-retest variability of each measurement. Two hundred forty-two volunteer participants had a HRTTE study to measure their LAD wall thickness, lumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…The lumen diameter of the left main coronary is 4 mm and the diameter of the distal left anterior descending artery (LAD) is 2.7 mm, consistent with the range of diameters on normal human left coronaries, the proximal LAD diameter d = 3.7 ± 0.4 mm, and distal LAD d = 1.9 ± 0.4 mm. 41,42 The wall structural mesh was obtained using a uniform wall thickness h = 0.08 mm ( Figure 2). The coronary wall thickness is consistent with two electrocardiographic studies that consistently reported a coronary wall thickness of 1.0 ± 0.2 mm 42,43 and with the morphometric law for coronary vessel thickness by Podesser, 44 and larger than a typical vessel wall thickness equal to 10% of the vessel radius found in the literature.…”
Section: Sub-models For the Coronary Circulation With Deformable Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lumen diameter of the left main coronary is 4 mm and the diameter of the distal left anterior descending artery (LAD) is 2.7 mm, consistent with the range of diameters on normal human left coronaries, the proximal LAD diameter d = 3.7 ± 0.4 mm, and distal LAD d = 1.9 ± 0.4 mm. 41,42 The wall structural mesh was obtained using a uniform wall thickness h = 0.08 mm ( Figure 2). The coronary wall thickness is consistent with two electrocardiographic studies that consistently reported a coronary wall thickness of 1.0 ± 0.2 mm 42,43 and with the morphometric law for coronary vessel thickness by Podesser, 44 and larger than a typical vessel wall thickness equal to 10% of the vessel radius found in the literature.…”
Section: Sub-models For the Coronary Circulation With Deformable Wallsmentioning
confidence: 99%
“…41,42 The wall structural mesh was obtained using a uniform wall thickness h = 0.08 mm ( Figure 2). The coronary wall thickness is consistent with two electrocardiographic studies that consistently reported a coronary wall thickness of 1.0 ± 0.2 mm 42,43 and with the morphometric law for coronary vessel thickness by Podesser, 44 and larger than a typical vessel wall thickness equal to 10% of the vessel radius found in the literature. [45][46][47][48][49] Interaction between fluid and structure is simulated through Arbitrary Lagrangian-Eulerian (ALE) coupling provided by the SimVascular svFSI solver, which implements a variational multi-scale finite element method with second order implicit generalized-α time integration.…”
Section: Sub-models For the Coronary Circulation With Deformable Wallsmentioning
confidence: 99%
“…Leung et al [34] other comparisons are hard to make since the location of the distal section is not always clear [36]. Measurements might also vary between human [33] and porcine specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The normal diameter is about 3.21 mm, the diameter of stenotic area is 1.43 mm, and the wall thickness is 1 mm [14] [15].…”
Section: Reconstruction Of Right Coronary Arterymentioning
confidence: 99%